Proton pump inhibitor intake negatively affects the osseointegration of dental implants: a retrospective study - Altay, Mehmet Ali; Sindel, Alper; Özalp, Öznur; Yıldırımyan, Nelli; Kocabalkan, Burak (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2019)
This study sought to investigate the association between the systemic intake of proton pump inhibitors (PPI) and the early failure of dental implants. A retrospective cohort study involving 1,918 dental implants in 592 patients (69 implants in 24 PPI users and 1,849 implants in 568 nonusers, respectively) was conducted. The effect of PPI intake on the osseointegration of dental implants was evaluated using patient- and implant-level models. Among 24 PPI users, two patients experienced implant failure, one of whom had three and the other of whom had one failed implant, respectively. Thus, the rate of failure for this population was 8.3%. Separately, 11 nonusers each experienced one implant failure, and the failure rate for these patients was 1.9%. Fisher's exact test revealed statistically significant differences between PPI users and nonusers at the implant level ( =0.002) but failed to show any significance at the patient level ( =0.094). The odds of implant failure were 4.60 times greater among PPI users versus nonusers. Dental implants that were placed in patients using PPIs were found to be 4.30 times more likely to fail prior to loading. The findings of this study suggest that PPI intake may be associated with an increased risk of early dental implant failure.